From 'OPAT' to 'COpAT': implications of the OVIVA study for ambulatory management of bone and joint infection. (15th April 2019) - Seaton, R A; Ritchie, N D; Robb, F; Stewart, L; White, B; Vallance, C
Abstract: Bone and joint infection contributes significantly to clinical activity within outpatient parenteral antimicrobial therapy (OPAT) services. The OVIVA (oral versus intravenous antibiotics for bone and joint infection) randomized study has challenged the practice of prolonged intravenous therapy, because non-inferiority of oral antibiotic therapy was demonstrated, thereby implying that early transition to oral therapy is an appropriate alternative to prolonged intravenous therapy. We examine the caveats to the study and discuss the implications for OPAT practice, highlighting the importance of careful oral antibiotic selection with attention to bioavailability, bone penetration, drug interactions, compliance and toxicity monitoring. We emphasize that ambulatory antibiotic therapy (whether intravenous or oral) in this patient group requires expert multidisciplinary management, monitoring and follow-up, and ideally should be undertaken within existing OPAT or, more accurately, complex outpatient antibiotic therapy (COpAT) services.